0 - Editorial: Continuing the Erosion of Disciplinary Frontiers in the Study of Africa: by Ebrima Sall & Ato Kwamena Onoma - Sall, Ebrima; Onoma, Ato Kwamena (CODESRIA Bulletin, 2021)
Ours is the era of the anthropocene; the age in which the human factor is, it is agreed, probably more determining in almost everything than it has ever been. The very first question that this raises is how to understand this era, and finding answers to that question requires the full mobilization of the humanities and social sciences. It also calls for a repositioning of the disciplines in order to make them speak to each other in ways that could make multidisciplinarity and transdisciplinarity truly meaningful. Another question that arises is that of how to build a new ‘civilization’, which, after all, is what ‘development’ according to one of the founders of CODESRIA, Professor Samir Amin, should be about. The new civilization will be ecological and characterized by all the good things that make our societies, economies and governance systems, and our world more inclusive, just, and accommodating; in short: democratic and ‘developing’. It would certainly not be ‘dreamland’ or nirvana, but one where the ‘good life’ for the individual and collective would not seem totally unrealizable. The need for us (human beings) to rethink and renegotiate our relationship with the other inhabitants of our planet has now been widely recognized. The difficulty has been that of translating the new awareness that the holding of global forums, summits and conferences, such as the COP21 (held in Paris in 2015) and COP22 (recently held in Marrakech), and the adoption of the Sustainable Global Development Goals by the UN Summit held in New York in September 2015 into concrete policies and practical measures. That difficulty is not merely a ‘technical’ difficulty: it has to do with the very nature of the power relations that are embedded in social, economic and political relations at the local, national, regional and global levels. Redefining our relations with the other inhabitants of our planet therefore goes hand-in-hand with the renegotiation of social, economic, political, gender and other kinds of relations within and between our societies across the globe. Inequality has been one of the dominant traits of those relationships, as the debates at the third edition of the World Social Science Forum cohosted by the International Social Science Council, the Human Sciences Research Council of South Africa, and CODESRIA in Durban, in September 2015, have shown.1 It follows from the above that we must also raise a third question: how to redefine humanism and, in the African context, perhaps give a new meaning to ‘Ubuntu’. Indeed, ‘I am because you are’, and because the planet and the other inhabitants of it also are. The point was again clearly made in several of the research-based convenings that CODESRIA held or co-hosted, including a conference on security regimens in today’s Africa; a conference on the (Re)making of African Bodies; and a workshop on Re-thinking Education in Africa; but also in a series of ‘thought workshops’ (ateliers de la pensee) that brought together thought leaders among whom were not only scholars in the conventional sense, but also writers, philoso- phers, historians, journalists, and activists, and many other events. The complexity of the challenges facing our world is such that few, if any, are the issues that any single discipline could claim to be able to deal with in a comprehensive and satisfactory manner. To respond adequately to the challenges posed by HIV/AIDS, climate change, and the Ebola Virus Disease (EVD), to name a few, many, if not all the disciplines had to be mobili- zed. The number of initiatives, such as ‘Future Earth’, that deliberately seek to bring both the natural sciences and the social and human sciences together is therefore increasing. That also is the reason why global institutions such as the Interna- tional Social Science Council (ISSC) of which CODESRIA is a member) and the International Council for Science Unions (ICSU) have decided to consider merging to form one global science council that would be capable of facilitating the dialo- gue and cooperation (that have not always been easy to foster) between the natural sciences and the social sciences, humanities, engineering, and other sciences. Whether or not this would be a wise thing to do is a matter of debate. The point we are making here is that there is growing awareness and acknowledgement of the fact that no science, discipline, area of or field of study can provide the answers to all the questions we are as- king. In practice, however, certain disciplines, particularly the social sciences and humanities, are still struggling for recogni- tion, and adequate resources to be able to make even great contributions to the study and overcoming of the challenges facing our contemporary world. That struggle is also going on between the social sciences and the humanities, both at the global level, and within Africa. In some sense, that is also an aspect of the power dynamics that exist within the knowledge production world itself that World Social Science Report 2010 (on Knowledge Divides) focuses on. CODESRIA has also been speaking to that issue in our research and training programmes, but also in a number of other initiatives, such as the following: spearheading the adoption of a declaration of the Global South on open access, debating the colonial library; re-visiting the Kampala Declaration on Intellectual Freedom and Social Res- ponsibility; developing an African Citation Index, or, simply, launching an Africa Review of Books. CODESRIA’s African Humanities Programme has been one important vehicle through which the Council has been making targeted interventions aimed at promoting the humanities. The programme was laun- ched way back in the late 1990s, and has contributed to the ad- vancement of the humanities on the continent in no small way. On August 28-29, 2015 a planning meeting was held by CODESRIA and the University of Ghana, Legon to reflect on the location of the Humanities in the life and work of CODESRIA, particularly in these times of multilayered transformations going on in Africa and in the world around us. The meeting assembled around 20 leading scholars from the Social Sciences and Humanities, artists, senior officials of the University of Ghana and members of the CODESRIA Secretariat for two days. Issues debated included CODESRIA’s long history of work in the Humanities, the situation of the Social Sciences and Humanities in the age of STEM and thematic priorities for the Council’s work in the Humanities going forward. The partnership between CODESRIA and the University of Ghana, Legon, which had overseen the highly successful African Humanities Institute, and which continues to anchor the Council’s Humanities Programme was also the subject of much discussion. Some of the think pieces from that meeting are published in this edition of the CODESRIA Bulletin. The planning meeting was testament to the recognition of the need to approach the continued interaction of these two broad areas of study within CODESRIA in a self-conscious way that maximizes the benefits to the scholars involved as well as the Council. Despite forays into futures studies, the Social Sciences and their emphasis on incrementalism and on descriptive and explanatory analysis in knowledge production are inherently too tied to what is, thus limiting their ability to broach new worlds in an era where alternative futures are seen as increasingly important subjects of study and research. The transgressive spirit which informs the Humanities makes them better at imagining other worlds, but this penchant for contemplation of what could be have often led to talk of ‘useless’ flights of fantasy. Through dialogue, the Social Sciences can help ground the Humanities in what is and the Humanities, in turn, can help the Social Sciences better use a focus on what is to reflect on what could be. There are two broad ways of imagining the location of the Huma- nities within CODESRIA. The first of these involves the creation of a special space where scholars in the Humanities can carry out their work in CODESRIA. This would predominantly be a site of intra-Humanities dialogue within the broader context of CODESRIA. The second form involves the integration of work in the Humanities into the life and work of CODESRIA in ways that are not different from what is done for the Social Sciences. This involves creating one space where the Social Sciences and Humanities can dialogue with each other. If we imagine these as the two poles of a continuum, we face the question of toward which pole the approach of CODESRIA should be inclined. In broaching this challenge one can pose four questions on how best to locate the Humanities in the life and work of CODESRIA, a self-described organization for Social Science research: Which form of incorporation best enables us to profile and sell the work of CODESRIA in the Humanities? Here, the idea of a special space for the Humanities seems to have cer-tain advantages. Instead of diluting the Humanities in a broader pool, it gives us a special set that can be made visible (named, given a logo, etc.), promoted, used for fundraising and reported on. Which form of incorporation best fosters the mutual enhan- cement of the substance of work in the Humanities and Social Sciences? Here a special space seems to promise a more commodious and secure environment in which scholars in the Humanities can operate without getting marginalized by the bigger social scientific community. This, however, raises the specter of ghettoization and lacks the benefits highlighted above that a truly integrated inter- disciplinary arrangement can bring about. Which form of incorporation best enables the Council to capture the nature, extent, quality and impacts of its work involving the Humanities? It is clear that limiting the Council’s work in the Humanities to that done under a ‘Humanities Programme’ greatly obfuscates by ensuring that extensive involvement of Humanities scholars in many of the Council’s other activities go unaccounted for. Which form of incorporation of the Humanities will best help CODESRIA reinforce its position as the foremost African social science research council and leading contributor to knowledge production and dissemination in Africa? Given the Council’s continued focus on ‘the making of African futures,’ an intimate interdisciplinary dialogue resulting from the thorough integration of the Humanities in the work of the Council can only be thought of as necessary. In the event that one agrees on the overall advantages of privi- leging intimate interdisciplinary dialogues in accommodating the Humanities in the life and work of CODESRIA, a provocative question has once in a while been raised: should we contemplate the remaking of CODESRIA as the Council for the Development of Social Research in Africa instead of the Council for the Development of Social Science Research in Africa? The change in the name of the Council from being called a Council for the Development of Economic and Social Science Research (CODESRIA), to Council for the Development of Social Science Research (CODESRIA) that was made by the 7th General As- sembly in 1992 was already an attempt to make the name reflect the diversity of the social sciences, broadly defined. Beyond changes in the name of the Council, the issue really is that of keeping pace with developments in our community and in the world around us, and finding the best possible institutional type and mode of operation that could enable CODESRIA to remain truthful to its mission and fulfill its mandate. A conference organized on 3-4 November 2016 by CODESRIA and the Mwalimu Nyerere Professorial Chair in Pan-African Studies of the University of Dar es Salaam demonstrates some of the handsome fruit that social research as a thoroughly integra- ted exercise can bear. Focusing on the multiple and changing practices of modifying living bodies in Africa, the conference brought together a wide range of people including social scien- tists, scholars in the humanities, dermatologists, beauticians and clinical psychiatrists and psychotherapists. Issues including the bleaching of bodies, ‘tribal’ marks, breast-ironing, tattooing and forms of FGMFemale genital ambiton were addressed from multiple disciplinary perspectives shed significant light on this phenomena. A brief report on this mee- ting whose theme was, ‘(Re) making bodies: The structures and dynamics of aesthetics and aspirations in an evolving Africa,’ is included in this edition of the Bulletin. In the spirit of continuing these forms of engagement, the Council has selected "‘Emergence’ on screen and on stage" as the theme of its next bi-annual workshop to be held during the Pan-Africa Film and Television Festival- FESPACO. The workshop will be held on 27-28 February 2017 in Ouagadou- gou, Burkina Faso. It hopes to attract scholars from across the Humanities and Social Sciences as well as artists and practitioners to discuss the idea of emergence that is today a leading leitmotif on the screen and stage of the artist, politician and development practitioner alike. Are we not already living the Council for the Development of Social Research in Africa?